A Review Of Sustainable Development Of Geothermal Energy (UIR PRESS, 2025)
Renewable energy is certainly more environmentally friendly because it can reduce air pollution and environmental damage due to exploration. The costs incurred to produce energy are cheaper because the energy source is free. Electricity is important now, but the obstacle faced is how to reduce and replace fossil energy because if it is continuously used, it will hurt the world. The best solution is to replace it with new renewable energy, such as geothermal energy, which has great potential in Indonesia. This research was conducted using a qualitative descriptive research method. The data used in this study were taken through in-depth interviews with an expert and a literature study from various relevant sources. The data was collected through in-depth interviews based on the IAEA's Sustainable Development Energy Indicator framework, which Prof. Thierry Lefèvre simplified. The results of the in-depth interviews are then combined with relevant data and literature.